2002
DOI: 10.1021/ol0261938
|View full text |Cite
|
Sign up to set email alerts
|

Ring Strain and Its Effect on the Rate of the General-Base Catalyzed Enolization of Cyclobutanone

Abstract: [reaction: see text] The 3-quinuclidinone-catalyzed (pK(BH) = 7.5) enolization of cyclobutanone (1) in D(2)O at 25 degrees C, I = 1.0 (KCl) was followed by deuterium incorporation, which was determined by (1)H NMR. The second-order rate constant for the buffer-catalyzed deprotonation of 1 was found to be k(B) = 3.3 x 10(-4) M(-1) s(-1), which is compared to rates for acetone and 2-(2'-oxopropyl)benzaldehyde under similar conditions. The data shows that ring strain has very little effect on the energy barrier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
3
8
2
Order By: Relevance
“…This could be compared to k DO acetone /k DO cyclobutanone of ∼4 (see below), and k B for the 3-quinuclidinone-catalyzed reaction under similar conditions (k B acetone /k B cyclobutanone = 1.6) 37,47 As previously noted, these results illustrate the similarity in the reactivity of acetone and cyclobutanone over a wide range of general base catalyst. 47 The secondorder rate constant for the deuteroxide-catalyzed enolate formation for acetone (k DO = 0.21 M -1 s -1 , determined in D 2 O, at 25 °C, I = 1.0 M (KCl)), was approximately the same as the value reported for the hydroxide-catalyzed enolization of acetone (k HO = 0.22 M -1 s -1 ) in H 2 O, at 25 °C, I = 0.1 (NaCl). 52 This result was somewhat unexpected as a k DO for acetone has been estimated to be k DO = 0.32 M -1 s -1 based upon a solvent isotope effect of k DO /k HO = 1.4.…”
Section: Jocarticlesupporting
confidence: 53%
See 1 more Smart Citation
“…This could be compared to k DO acetone /k DO cyclobutanone of ∼4 (see below), and k B for the 3-quinuclidinone-catalyzed reaction under similar conditions (k B acetone /k B cyclobutanone = 1.6) 37,47 As previously noted, these results illustrate the similarity in the reactivity of acetone and cyclobutanone over a wide range of general base catalyst. 47 The secondorder rate constant for the deuteroxide-catalyzed enolate formation for acetone (k DO = 0.21 M -1 s -1 , determined in D 2 O, at 25 °C, I = 1.0 M (KCl)), was approximately the same as the value reported for the hydroxide-catalyzed enolization of acetone (k HO = 0.22 M -1 s -1 ) in H 2 O, at 25 °C, I = 0.1 (NaCl). 52 This result was somewhat unexpected as a k DO for acetone has been estimated to be k DO = 0.32 M -1 s -1 based upon a solvent isotope effect of k DO /k HO = 1.4.…”
Section: Jocarticlesupporting
confidence: 53%
“…45,46 In contrast to these earlier results, our studies showed that sensitivity of cyclobutanone to a general base catalyst was similar to that found for acetone and a phenylacetone derivative. 47 These results 47 pointed to a conclusion that ring strain did not have an apparent effect on the reactivity of cyclobutanone vs that of other ketones, contradicting the results of other studies. 45,46 The question of why cyclobutanone (2) has not been as thoroughly investigated as other ketones was not due to a lack of interest in the compound itself but rather to experimental limitations of the halogenation technique that was the primary method used to follow enolate generation in solution.…”
Section: Introductionmentioning
confidence: 84%
“…The addition of anhydrous magnesium bromide etherate (or magnesium bromide) prior to addition of cyclobutanone was necessary in most cases to obtain satisfactory yields of the isolated carbonyl addition product. The yields for this reaction varied from 55 to 89% 2 Formation of Cyclobutanols 4 a − g …”
Section: Resultsmentioning
confidence: 99%
“…As the point of departure, the readily available cyclohexadiene acetonide 8 was found to participate in an exquisitely stereo‐ and regioselective [2+2] cycloaddition that furnished 9 in excellent yield (Scheme ) 12. Diastereoselective introduction of the requisite aryl amine was achieved through the aegis of ortho‐metallated aniline 10 ,13 which proved uniquely effective for this transformation as attempts with numerous other aryl metal species led to enolization or decomposition 14…”
Section: Methodsmentioning
confidence: 99%